Electric Consumption by Industrial Enterprises; Modeling, Rationing and Forecasting - Rakhmonov I. U. Ikromjon Usmonovich; Ushakov V. Ya. Vasily Yakovlevich; Khoshimov F. A. Foziljon Abidovich; Niyozov N. N. Numon Nizomiddinovich; Kurbonov N. N. Nurbek Nurullo ugli; Mytnikov A. V. Aleksey Vladimirovich (Power Systems)
Заглавие с титульного экрана